In vitro study of effective factors for the inhibitory assay on pancreatic lipase - Tran, The Huan; Ho, Thi Thu Trang; Cao, Thi Cam Nhung; Ho, Hoang Nhan; Tran, Thai Son (Tạp chí Y Dược Huế, 2023)
Background: Pancreatic lipase is one of the safest targets of anti-obesity drugs. To date, orlistat is the only pancreatic lipase inhibitor approved for the long-term treatment of obesity. Therefore, there is an elevated need to find new drugs for this disease. Determining the factors affecting the test to evaluate pancreatic lipase inhibitory activity in order to build a standard assay procedure is necessary. This will make it much easier for researchers to find novel compounds that inhibit the enzyme. Materials and method: The current study investigated the factors influencing pancreatic lipase activity and evaluated the enzyme inhibition of orlistat by spectrophotometric method at 405 nm using p-nitrophenyl palmitate as a substrate. Results: With the optimized conditions, the test to evaluate pancreatic lipase inhibitory activity of orlistat gave results similar to those published by other authors. Conclusion: The methodology of this work should be applied in the studies looking for new effective drugs to treat obesity.